Persepsi Visual Merek Adidas di Feed Instagram Pada Gen Z - Hidayatillah, Tiara Eka; Istiqomah, Istiqomah (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study aims to analyze and understand how visual elements in the @adidasindonesia Instagram feed shape Adidas brand perception among Generation Z. This study uses Charles Morris's visual perception theory framework which includes three main aspects, namely syntactic, semantic, and pragmatic, to examine visual structure, meaning, and visual impact on the audience. The research method used is qualitative with a descriptive approach, which focuses on an in-depth understanding of the audience's visual perception without involving hypothesis testing or statistical measurements. The object of the study is the visual content on the @adidasindonesia Instagram feed during the period 2023 to 2025. Data were obtained through in-depth interviews with five Generation Z informants selected using a purposive sampling technique, and supported by observations of the visual characteristics of Instagram posts. The results of the study indicate that the visual feed of @adidasindonesia Instagram has a strategic role in shaping the perception of the Adidas brand among Generation Z. Syntactically, the consistency of design, visual composition, and the use of Adidas's distinctive identity elements are considered capable of creating strong visual readability and brand recognition. Semantically, Adidas's Instagram visuals are interpreted not only as a means of product promotion, but also as a representation of an active lifestyle, community values, inclusivity, modernity, and sustainability. Meanwhile, pragmatically, Adidas's Instagram visual feed has a real impact on audience interest, the formation of emotional closeness and trust in the brand, as well as encouraging product information searches and strengthening brand loyalty. Based on these findings, it can be concluded that the visual strategy of Instagram @adidasindonesia is effective in building positive perceptions and maintaining the relevance of the Adidas brand amidst the dynamics of Generation Z's digital culture.